2020
DOI: 10.2147/oajsm.s237997
|View full text |Cite
|
Sign up to set email alerts
|

<p>Epidemiological Data on LCL and PCL Injuries Over 17 Seasons in Men’s Professional Soccer: The UEFA Elite Club Injury Study</p>

Abstract: Background: There is limited epidemiological information on injury rates and injury mechanisms for lateral collateral ligament (LCL) and posterior cruciate ligament (PCL) injuries in male professional soccer. In addition, time trends and lay-off times for these injuries have not yet been determined. Aim: To determine injury rates and circumstances of LCL and PCL injuries over 17 seasons in men's professional soccer. Methods: A prospective cohort study, in which 68 professional European soccer teams were follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 27 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…In addition, an epidemiological study demonstrated a median lay-off time of 31 days after PCL injury for professional male soccer players. However, these prospectively collected data in men’s professional soccer included all grades of PCL injuries as well as operatively and non-operatively treated athletes [ 48 ]. Accordingly, initial non-operative management based on functional bracing and rehabilitation with optional delayed PCL-R seems to be reasonable for isolated acute PCL injuries, even for high-level athletes with grade III PCL injuries [ 2 ].…”
Section: Non-operative Treatment Rehabilitation and Return-to-sportmentioning
confidence: 99%
“…In addition, an epidemiological study demonstrated a median lay-off time of 31 days after PCL injury for professional male soccer players. However, these prospectively collected data in men’s professional soccer included all grades of PCL injuries as well as operatively and non-operatively treated athletes [ 48 ]. Accordingly, initial non-operative management based on functional bracing and rehabilitation with optional delayed PCL-R seems to be reasonable for isolated acute PCL injuries, even for high-level athletes with grade III PCL injuries [ 2 ].…”
Section: Non-operative Treatment Rehabilitation and Return-to-sportmentioning
confidence: 99%
“…Understanding the causes and epidemiology of PCL injuries is essential in identifying risk factors and developing effective prevention strategies. 4…”
Section: Introductionmentioning
confidence: 99%